The portrayal of Rohingya refugees in Indonesian news media: A corpus-assisted critical discourse analysis - Imam Munandar; Yunie Amalia Rakhmyta; Rahmanita Zakaria; Sungkawati Kardi Wahyuningsih (Studies in English Language and Education, 2024)
This research investigated the representation of Rohingya refugees stranded in Aceh province in the Indonesian news media during the four-year crisis between 2020 and 2023. The study aimed to examine how Rohingya refugees were represented in the media during the crisis using the Critical Discourse Analysis and the Discourse Historical Approach (DHA). The research employed a mixed method analysis to analyse the corpus data of 46,769 words extracted from 62 news articles published in two mainstream Indonesian publications, namely the regional Serambi Indonesia and the national Jakarta Post, between June 24, 2020, and March 27, 2023. Using corpus linguistics and Van Dijks CDA, the research uncovered four prominent argumentation strategies used in the media to portray the refugee crisis. Serambi Indonesia and the Jakarta Post utilised the Humanitarianism and Administration argumentation the most, concentrating on precarious conditions and efforts to handle the influx of refugees. Nevertheless, the local daily Serambi Indonesia used some Threat/Danger argumentation, portraying refugees as dangers and threats to local safety. The study further reveals how the medias alignment with the government agenda is decisive for the press to construct public narratives. The narrative is expected to influence peoples attitudes and behaviours toward refugees in the province of Aceh.